Association between Dental Variables and Hashimoto's Disease: A Retrospective Cohort Study - Peršić Bukmir, Romana; Paljević, Ema; Vidas Hrstić, Jelena; Božac, Elvis; Mocny-Pachonska, Katarzyna; Brekalo Pršo, Ivana (European Journal of Dentistry, 2025)
Objectives The present study aimed to compare dental, endodontic, and periodontal status in patients with Hashimoto's disease and healthy patients, as well as to disclose the relation between dental variables and Hashimoto's disease.Materials and Methods The research included 85 patients affected by Hashimoto's thyroiditis (analyzed group) and 85 healthy patients (control group). The two groups were matched according to age and gender. Data regarding patients' health status was acquired from their medical records. Data regarding dental, endodontic, and periodontal status were acquired from patients' dental records and digital panoramic radiographs.Statistical Analysis Since a nonnormal distribution of data was detected, a median and interquartile range were used as a measure of central tendency and dispersion. Mann–Whitney U test and chi-squared test were used to test the differences between the groups. Multiple linear regression analysis and logistic regression analysis were used to test the association of the data.Results Healthy participants had significantly higher median number of teeth with secondary caries (median 2; interquartile range 1–3) when compared with participants with Hashimoto's disease (median 1; interquartile range 0–2; p < 0.001). Periodontal disease was present in significantly more participants with Hashimoto's disease than healthy patients (68.2% vs. 45.9%; chi-square = 7.779; p = 0.005). The presence of Hashimoto's disease increased the risk of periodontal disease presence three times (odds ratio [OR] = 3.14; 95% confidence interval [CI] 1.38–7.15; p = 0.007). The presence of periodontal disease increased the risk of Hashimoto's disease presence by 2.5 times (OR 2.54; 95% CI: 1.36–4.73; p = 0.004).Conclusion With the study limitations in mind, it may be concluded that a positive relationship between periodontal disease and Hashimoto's thyroiditis exists.
Keywords: dental caries; Hashimoto disease; periapical periodontitis; periodontitis